The Chromosome 18 Clinical Resource Center. Issue 3 (30th March 2018) - Cody, Jannine D.; Hasi‐Zogaj, Minire; Heard, Patricia; Hill, Annice; Rupert, David; Sebold, Courtney; Soileau, Bridgette; Hale, Daniel E.
Abstract: Background: The Chromosome 18 Clinical Research Center has created a pediatrician‐friendly virtual resource center for managing patients with chromosome 18 abnormalities. To date, children with rare chromosome abnormalities have been cared for either symptomatically or palliatively as a reaction to the presenting medical problems. As we enter an era of genomic‐informed medicine, we can provide children, even those with individually unique chromosome abnormalities, with proactive medical care and management based on the most contemporary data on their specific genomic change. It is problematic for practicing physicians to obtain and use the emerging data on specific genes because this information is derived from diverse sources (e.g., animal studies, case reports, in vitro explorations) and is often published in sources that are not easily accessible in the clinical setting. Methods: The Chromosome 18 Clinical Resource Center remedies this challenging problem by curating and synthesizing the data with clinical implications. The data are collected from our database of over 26 years of natural history and medical data from over 650 individuals with chromosome 18 abnormalities. Results: The resulting management guides and video presentations are a first edition of this collated data specifically oriented to guide clinicians toward the optimization of care for each child. Conclusion: The chromosome 18 data and guides also serve as models for an approach to the management of any individual with a rare chromosome abnormality of which there are over 1, 300 born every year in the US alone. Abstract : The Chromosome 18 Clinical Research Center has created a physician‐friendly virtual resource center for managing patients with chromosome 18 abnormalities. The resources include management guides for 18p‐, 18q‐, Tetrasomy 18p, and Ring 18 in multiple web‐based formats.